Effects of a combined transcranial magnetic stimulation (TMS) and cognitive training intervention in patients with Alzheimer's disease. Issue 4 (16th January 2020) - Sabbagh, Marwan; Sadowsky, Carl; Tousi, Babak; Agronin, Marc E.; Alva, Gustavo; Armon, Carmel; Bernick, Charles; Keegan, Andrew P.; Karantzoulis, Stella; Baror, Eyal; Ploznik, Moran; Pascual‐Leone, Alvaro
Abstract: Introduction: This clinical trial evaluates the efficacy and safety of a 6‐week course of daily neuroAD™ therapy. Methods: 131 subjects between 60 and 90 years old, unmedicated for Alzheimer's disease (AD), or on stable doses of an acetylcholinesterase inhibitor and/or memantine, with Mini–Mental State Examination scores between 18 and 26, clinical dementia rating scale scores of 1 or 2, enrolled for a prospective, randomized, double‐blind, sham‐controlled, multicenter clinical trial. Structural brain MRIs were obtained for transcranial magnetic stimulation targeting. Baseline Alzheimer's disease assessment scale—cognitive (ADAS‐Cog) and Clinical Global Impression of Change were assessed. 129 participants were randomized to active treatment plus standard of care (SOC) or sham treatments plus SOC. Results: Subjects with baseline ADAS‐Cog ≤ 30 ( 85% of study population) showed a statistically significant benefit favoring active over sham. Responder analysis showed 31.7% participants in the active group with ≤ −4 point improvement on ADAS‐Cog versus 15.4% in the sham group. Discussion: neuroAD™ Therapy System provides a low‐risk therapeutic benefit for patients with milder AD (baseline ADAS‐Cog ≤30) beyond pharmacologic SOC.